Early Chinese Voyaging in the South China Sea: Implications on Territorial Claims - Michael Flecker (Diponegoro University, 2017)
The main purpose of this paper is to examine historically issues of territorial claims over the South China Sea. As it is known that at present there are at least six countries claiming part or all of South China Sea territory. In this case China is the most ambitious country to control all areas in the South China Sea. This has led to political and military tensions in the region. It is strange that the South China Sea waters has actually been a shipping thoroughfare for the last two millennia. Therefore, this historical study will contribute to an understanding of the issues that could provoke international conflict.